O currículo crítico-libertador respondendo aos desafios do contexto intergeracional nas salas da EJA - Zanardo, Nivia Dantas Ribeiro (2017)
In view of the difficulties presented by teachers, managers and researchers regarding how to work with young people, adults and the elderly, with very different profiles that compose the classrooms of the Youth and Adult Education (called EJA), this research proposed to investigate possibilities for the construction of a curriculum, based on Freirean references, that can respond to the intergenerational context. The theoretical reference used to understand and analyze the data produced was based mainly on Freirean categories and on authors who research the profiles of the Youth and Adult Education. The field study had a qualitative approach and was developed through a case study in a school unit that specifically offers the Youth and Adult Education. The procedures used were semi-structured interviews with teachers, students, management team and pedagogical guides. The elements identified, from the answers of the different subjects and in the light of the Freirean categories, were analyzed and compared with the documents produced by the Municipal Department of Education of São Bernardo do Campo. We highlight the factors that colaborate for a school that engages itself to work with a critical-liberating proposal in order to meet the circumstances of the EJA’s intergenerational classrooms. It is therefore proposed to indicate ways that contribute to the education of teachers in this modality of education